Coaches’ Psychological Well-Being and Positive Thinking Skills - Abdulselam Kahraman; Veysel Temel (Journal of Educational Issues, 2024)
This study was conducted to examine the psychological well-being and positive thinking skills of the participants who participated in the inter-institutional volleyball tournament organized by the Karaman volleyball provincial representative in 2022. The population of the research consists of 288 participants (28 teams), 15 of whom are female and 273 are male. Positive Thinking Skills Scale Developed by Bekhet and Zauszniewski (2013) and adapted to the Turkish by Akın et al. (2015) for 145 of the participants and the short form of “Psychological Well-Being Scale” developed by Ryff (1989) and created by Akın et al. (2012) were applied. According to the results of the research, it can be concluded that she has psychological well-being levels below the mid-level and she has a positive thinking level above the mid- level. As a result of the correlation analysis, it was determined that there was a statistically low level of positive correlation at the p < .01 level (r = .229; p < .01) between the psychological well-being test scores and the positive thinking test scores. In terms of variables, it can be concluded that individuals who do team sports have higher levels of psychological well-being and positive thinking than those who do individual sports, and participants who do sports 4 days a week have higher levels of psychological well-being than those who do sports 3 and 1 days a week.